2013
DOI: 10.1001/jamaoto.2013.1821
|View full text |Cite
|
Sign up to set email alerts
|

Posttonsillectomy Hemorrhage in Children With von Willebrand Disease or Hemophilia

Abstract: The frequency of immediate posttonsillectomy hemorrhage in children with VWD or hemophilia is similar to rates in the general healthy population. However, among children with VWD or hemophilia, the rate of delayed hemorrhage is substantially higher, especially in older children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
0
17
0
2
Order By: Relevance
“…528 Further evidence of the safety and efficacy of surgical procedures comes from reviews of surgical outcomes in children with IBDs. [529][530][531] The most frequent interventions are circumcision, dental procedures, insertion of central venous access devices and tonsillectomy.…”
Section: General Perioperative Management Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…528 Further evidence of the safety and efficacy of surgical procedures comes from reviews of surgical outcomes in children with IBDs. [529][530][531] The most frequent interventions are circumcision, dental procedures, insertion of central venous access devices and tonsillectomy.…”
Section: General Perioperative Management Recommendationsmentioning
confidence: 99%
“…However, delayed haemorrhage occurred in 15%, substantially higher than the 1 to 3% reported in healthy patients. 530 Small case series studies in children with IBDs undergoing adenotonsillar procedures report variable rates of haemorrhage: lower, 532-535 similar, 536,537 or higher 538 than in healthy patients. These data suggest that perioperative protocols could be improved to reduce bleeding risk further.…”
Section: General Perioperative Management Recommendationsmentioning
confidence: 99%
“…Previous reports indicated that bleeding rates in children with known coagulopathies are between 2% and 17% [5][6][7][8]. Sun et al [7] reported that the rate of delayed hemorrhage after tonsillectomy in children with VWD or hemophilia was much higher, especially in older children. Considering all the relevant factors including the patient's condition, laboratory tests, the type of surgery, and the NHLBI recommendations [3], we followed the pediatrician's instructions.…”
Section: Discussionmentioning
confidence: 99%
“…Tonsillectomy is not a major surgery, but there is a high risk of bleeding during and after the procedure [4]. Previous reports indicated that bleeding rates in children with known coagulopathies are between 2% and 17% [5][6][7][8]. Sun et al [7] reported that the rate of delayed hemorrhage after tonsillectomy in children with VWD or hemophilia was much higher, especially in older children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation